BRIKET ARANG DARI SERBUK GERGAJIAN KAYU MERANTI DAN ARANG KAYU GALAM - Yuniarti Yuniarti; Yan Pieter Theo; Yogi Faisal; Arhamsyah Arhamsyah (Kementerian Perindustrian, 2011)
Saw dust waste has a big potential to be used as charcoal briquettes. The galam wood charcoal was added to increase the quality of the Meranti saw dust charcoal. The composition arrangement of Meranti saw dust and galam wood charcoal were 100%:0% ; 90%:10% ; 85%:15% ; 80%:20% ; and 0%:100%. Tapioca flour was used as the adhesive agent. We use 10.000 kg/cm2 for the pressure clamp. The result show that the charcoal briquette have the physical characteristics such as 3.78% - 4.54% for water content with the density between 0.49 – 0.77 gr/cm3 – 0,77 gr/cm3. For the chemical characteristics, the ash content is between 2.64% - 3.24%, substances fly content is 25,40% - 29,40% and the calorific value is between 5502.40 – 6249 cal/gr. The addition of galam wood charcoal is causing the decreasing of the ash and substance fly content but in contrast the calorific value and the residual carbon are increase.Keywords: charcoal briquette, meranti, galam, physic, chemistry